Introduction of complementary foods in premature infants - A. F. Kiosov; A. Yu. Pischalnikov (Лечащий Врач, 2024)
Background. In premature infants, when determining the beginning of the introduction of complementary foods, it is necessary to focus on the calendar and corrected age. It is considered possible to begin the introduction of complementary foods in premature infants at 4-6 months of calendar age. Complementary foods should not be offered to premature infants earlier than 3 months of corrected age. The time of formation of psychomotor skills is crucial for the introduction of complementary foods: the child must hold the trunk and head well, the ejection reflex has disappeared, chewing movements have appeared, the baby shows interest in new food. When solving issues related to the introduction of complementary foods in premature infants, it is necessary to use an individual approach. Premature babies often refuse to feed, have a low appetite and are more selective in food. Children need advice from a nutritionist, neurologist, gastroenterologist, speech therapist, psychologist. In children with bronchopulmonary dysplasia, damage to the nervous system, high-calorie nutrition may be required. In premature infants, when solving issues related to the choice of products, the sequence and speed of the introduction of complementary foods, it is necessary to focus on existing recommendations for full-term children. The beginning of the introduction of complementary foods in a premature baby is associated with the risk of excess or malnutrition. The complementary foods are introduced from a spoon before breastfeeding or formula feeding. Feeding is given slowly and gradually. All types of complementary foods are started with mono-component products. Individual order of introduction is possible. Tolerance should always be monitored. Currently, it is recommended to give preference to commercially produced complementary foods for premature infants. Such complementary foods are made from tested, high-quality raw materials and meet the strict hygienic safety requirements for infant nutrition. Commercially prepared complementary foods have a guaranteed composition, the necessary degree of grinding, and are enriched with vitamins and minerals.Conclusion. Vegetarian complementary foods are dangerous for premature babies due to the development of nutritional deficiencies. After the introduction of complementary foods in premature infants, breastfeeding should be continued.